Improving Gross Motor Ability Through Circuit Games For Children Group B - Khilati Adrikni (Prosiding University Research Colloquium, 2021)
This study aims to determine the improvement of gross motor skills through circuitgames for children aged group B in RA P2A Salaman. This type of research is classroomaction research that uses 2 cycles with stages including planning, implementation,observation and reflection stages. The research subjects were students of group B in RAP2A Salaman, totaling 16 children consisting of 9 girls and 7 boys. The data collectionmethod uses non-test in the form of observation. Based on the results of the research anddiscussion, it can be concluded that the gross motor skills of child B in RA P2A Salamancan be improved through circuit games. The increase that occurs can be seen from theresearch stage, namely observations made during pre-action, implementation of actionsin cycle I and cycle II. This is indicated by the results achieved by the subject from theinitial conditions or before the gross motor ability action was carried out in the lowcategory. Group B in RA P2A Salaman experienced an increase in gross motor skills frompre-cycle by 4.93%, increased in cycle I to 9.8% and increased to 12.8% in cycle II. Fromthese results it can be seen that the gross motor skills of children have reached thesuccess criteria expected by researchers.